Early and late morbidity of local excision after chemoradiotherapy for rectal cancer. Issue 3 (7th June 2021) - Teste, B; Rouanet, P; Tuech, J -J; Valverde, A; Lelong, B; Rivoire, M; Faucheron, J -L; Jafari, M; Portier, G; Meunier, B; Sielezneff, I; Prudhomme, M; et al.
Abstract: Background: Local excision (LE) after chemoradiotherapy is a new option in low rectal cancer, but morbidity has never been compared prospectively with total mesorectal excision (TME). Early and late morbidity were compared in patients treated either by LE or TME after neoadjuvant chemoradiotherapy for rectal cancer. Method: This was a post-hoc analysis from a randomized trial. Patients with clinical T2/T3 low rectal cancer with good response to the chemoradiotherapy and having either LE, LE with eventual completion TME, or TME were considered. Early (1 month) and late (2 years) morbidities were compared between the three groups. Results: There were no deaths following surgery in any of the three groups. Early surgical morbidity (20 per cent LE versus 36 per cent TME versus 43 per cent completion TME, P = 0.025) and late surgical morbidity (4 per cent versus 33 per cent versus 57 per cent, P < 0.001) were significantly lower in the LE group than in the TME or the completion TME group. of LE, was associated with the lowest rate of early (10 versus 18 versus 21 per cent, P = 0.217) and late medical morbidities (0 versus 7 versus 7 per cent, P = 0.154), although this did not represent a significant difference between the groups. The severity of overall morbidity was significantly lower at 2 years after LE compared with TME or completion TME (4 versus 28 versus 43 per cent grade 3–5, P < 0.001). Conclusion: The rate of surgical complications after neoadjuvant chemoradiotherapy in the LE group was half that of TME group at 1 month and 10 times lower at 2 years. LE is a safe approach for organ preservation and should be considered as an alternative to watch-and-wait in complete clinical responders and to TME in subcomplete responders. Abstract : Local excision (LE) is a new strategy for organ preservation but its morbidity post chemoradiotherapy is unknown in comparison to total mesorectal excision (TME). This study observed a significantly lower surgical morbidity of LE in comparison to TME, post neoadjuvant chemoradiotherapy for low rectal cancer, at 30 days (20% vs. 36%) and 2 years (4% vs. 33%) respectively. Local excision is a safe option for organ preservation in patients who are good responders to neoadjuvant therapy.